Identifying the key player in the diffusion network of global economic policy uncertainty - Shi, Kai; Nie, Li (Frontiers in Physics, 2024)
Within a generalized vector autoregressive framework comprising 22 country-level economic policy uncertainty indices, this study used a 12-period-ahead forecast error variance decomposition to compute spillovers. The results showed that although it has been in a downtrend since the third quarter of 2016, the overall spillover among the major economies remains high. Net spillover analyses in either the full or rolling samples illustrated that Singapore was the most decisive transmitter of spillovers, followed by Japan. Meanwhile, Ireland, the Netherlands, Russia, Brazil, Colombia, Italy, and Mexico were clear receivers of net spillover. After reorganizing the net pairwise spillovers into a directed weighted network, the core-periphery structure and backbone were extracted, and the diffusion centrality was calculated to ascertain the key player. Regardless of using the full or rolling samples, Singapore played an influential role in the diffusion network of global economic policy uncertainty.